Solution to the Political Problem of Bangsamoro: Maguindanaon Professionals and Employees Association Perspective - Usop, Annierah M (SOSIOHUMANIKA, 2012)
ABSTRACT: This study aimed to get the perspective of the Moro people in the Philippines islands, specifically members of MAPEA (Maguindanaon Professionals and Employees Association), on the belief that this sector could give an educated, intelligent, and strategic formula for the just, peaceful, and lasting solution to the political problem of the âBangsamoroâ people for self determination. In this study, an explanation based on the historical perspectives is necessity. It is to gather the answer of critical question, especially related to what are the root causes of the âBangsamoroâ political problem. Accordingly, the Philippine history is replete with many stories of rebellion and secession. In Mindanao alone, the government has been spending time, efforts, and resources to contend the armed movements. Besides, the âBangsamoroâ struggle for independence has started from 16th to 20th century. In 1968, after the Jabidah Massacre, MNLF (Moro National Liberation Front) fought against the government forces and the violent armed confrontations ended up in the peace talk in Tripoli, Libya in 1975. When in 1996, the GRP (Government of the Republic of Philippine) â MNLF Final Peace Agreement was forged, the MILF (Moro Islamic Liberation Front) continued the struggle so that the All-Out War declared by the Estrada administration in year 2000. Finally, the perspective of the members of MAPEA does not differ from what have already been done to solve the âBangsamoroâ political problem. Just like other organizations, they are hopeful that the conflict would end. This is a new learning. Key words: Moro people, historical perspective, self-determination, political problem and solution, and the perspective of MAPEA members.About the Author: Annierah M. Usop is a Ph.D. Student of the Philippine with major in Political Science at the School of Social Sciences and Humanities USM (Science University of Malaysia), 11800 Minden, Pulau Pinang, Malaysia. She can be reached at: asiyyahusop@yahoo.comHow to cite this article? Usop, Annierah M. (2012). âSolution to the Political Problem of Bangsamoro: Maguindanaon Professionals and Employees Association Perspectiveâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.5, No.1 [Mei], pp.123-134. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (March 15, 2012); Revised (April 20, 2012); and Published (May 20, 2012). Â  Â